Performance of Front Line Demonstrations in Hill Region of Uttarakhand - Papnai, Gaurav; Sachan, V K; Nautiyal, Pankaj; Manisha, Manisha (Indian Journal of Hill Farming, 2018)
Agriculture in hill regions of Uttarakhand is mainly dependent on rain. The scattered andun even land of hills hinders production of high yield. Various oilseed, cereals, pulses andvegetable crops were demonstrated at farmer’s field along with their farmers’ owned varieties and practices. All the recommended cultivation practices were performed to growthe crops. Front Line Demonstrations of improved technologies of major hill crops alongwith farmers’ practice were conducted during 2011-12 to 2013-14 at farmer’s field in hill region of Uttarakhand. The respondents were selected through purposive random selectionmethod as the data was to be collected from the adopted farmers for the demonstrations. Results revealed that the high yielding varieties of oilseed, cereals, pulses and vegetable crops have given more production as well as more economic benefit than the local varieties over the years. To gain more yield and benefit from the farming in hills and to cope up with such extreme conditions scientific methods can be adopted in these conditions.